Telegram Development in Dokeos-Based E-Learning As a Learning Media to Improve Students' Motivation in Learning Physics - Winarto, Anton; Hardyanto, Wahyu; Sugianto, Sugianto (Physics Communication, 2019)
Telegram Development in Dokeos-Based E-Learning as a Learning Media to Increase Students' Learning Motivation in Physics Subjects. The purpose of this study are to: (1) Determine the development of telegram in Dokeos-based e-learning as a learning media to increase students' motivation in physics subjects. (2) Analyse the effect of Telegram development learning media on dokeos-based e-learning to students' motivation. (3) Know the practicality of telegram learning media on dokeos-based e-learning according to the students. (4) Know the practicality of telegram learning media on dokeos-based e-learning according to the teacher. The type of this research is Research and Development (R&D). The results showed that: (1) Telegram learning media on dokeos-based e-learning were developed through seven stages, namely: needs and literature analysis, product design, product development, small-scale trials, product revisions, large-scale trials, and the final product. The learning media developed at the "AKPELNI" Semarang Sailing Vocational School presents physics material in Class X Nautika. (2) The learning media is feasible to be used in the Semarang "AKPELNI" Sailing Vocational School on Class X Nautika students. The feasibility of instructional media based on material experts included in the category strongly agreed with an average score of 87.5, while based on the media experts included the category strongly agreed with the average score of each indicator 85.71, based on the practicality of the media by students included in the high category that was a mean score of 3.36 out of 27 students, while based on the practicality of the media by teachers also a high category of 3.47 out of 2 physics teachers. (3) The use of telegram learning media on Dokeos-based e-learning is considered effective for increasing student motivation. This is proved by the increase of the average score in the N-Gain about 0.8, which includes in the high category.